If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 5x + -2xsquared = 0 Reorder the terms: 3 + -2adeqrsux + 5x = 0 Solving 3 + -2adeqrsux + 5x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -2adeqrsux + -3 + 5x = 0 + -3 Reorder the terms: 3 + -3 + -2adeqrsux + 5x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2adeqrsux + 5x = 0 + -3 -2adeqrsux + 5x = 0 + -3 Combine like terms: 0 + -3 = -3 -2adeqrsux + 5x = -3 Add '-5x' to each side of the equation. -2adeqrsux + 5x + -5x = -3 + -5x Combine like terms: 5x + -5x = 0 -2adeqrsux + 0 = -3 + -5x -2adeqrsux = -3 + -5x Divide each side by '-2deqrsux'. a = 1.5d-1e-1q-1r-1s-1u-1x-1 + 2.5d-1e-1q-1r-1s-1u-1 Simplifying a = 1.5d-1e-1q-1r-1s-1u-1x-1 + 2.5d-1e-1q-1r-1s-1u-1 Reorder the terms: a = 2.5d-1e-1q-1r-1s-1u-1 + 1.5d-1e-1q-1r-1s-1u-1x-1
| I^65= | | z=11z | | 14y^2=80 | | 6z-7z=4z-9-z | | 2=2m-5n | | 4x^2+84x-848=0 | | 64=-4(4k+4) | | 8t^3+27=0 | | -5x-2=1-4y | | 5(x+4)=x-3 | | 5x*5x-7=0 | | 4z-z=-5z-1-6z | | 11-(n-7)=3n+5 | | (2x-15)=7 | | 5(x+2)-2(3-2x)=-14 | | 1-(3-2(x-3))=2-(2x-1) | | 8[m+2n-p-7(2m-n+3p)]= | | 4x(1+5x)=20 | | 6(x+1)=3x-6 | | 12.6=0.62*t+8.3 | | -13=-3n+5-6n | | 9x-(4x-1)=16 | | bx-5b=4a-ax | | 3(2-3x)=33 | | 4-6(w+2)=10+5w | | z+2z+3z=180 | | 4.9t^2-20t-2=0 | | 4(2x-3)+2(x+2)=32 | | 8m+5=m | | 9n-12=3(3n-4) | | 75x-30=30x+60 | | ln(3x-15)=7 |